Signaling trust and reputation: The effect of certification and crowdfunding on donation intention for social entrepreneurship - Chaves Gastal, Luiza; Tondolo, Vilmar; Galve Araújo Silva, Napiê; Rauter Menezes, Gabrielito (Journal of Sustainable Competitive Intelligence, 2024)
Purpose: This study investigated the effect of external certification and registration on a crowdfunding platform on donation intentions for social projects, mediated by trust and reputation. Methodology/approach: This study employed a full-factorial vignette-based experiment. Participants were 151 potential donators. The hypotheses were tested through multiple regression analysis. Originality/Relevance: This study is one of the first to analyze the role of trust and reputation in mediating the effect of external certification and registration on a crowdfunding platform on donation intentions for social projects. Key findings: The results show that external certification and registration on crowdfunding platforms increase a project's trust and reputation, thus elevating donation intentions. Theoretical/methodological contributions: These findings highlight the importance of credibility and transparency signals in donor behavior. The research underscores how trust elements can positively influence donation decisions for social initiatives.